Hydrothermal Synthesis and Structural Properties of V205 Nanoflowers at Low Temperatures - Abd-Aighafour, N. M.; Ahmed, Naser. M.; Hassan, Z.; Almessiere, Munirah Abdullah (2017)
Vanadium pentoxide nanoflowers were synthesized through a simple hydrothermal method at low temperatures. The structure was fabricated using NH4V03 and oxalic acid as precursors with 0.1 M concentration. The morphology and structure of the nanoflowers were characterized by FESEM, XRD, Raman, and UV-Visible spectroscopy. The results reveal an orthorhombic structure with preferred orientation along (001) plane of the prepared V205 nanoflowers. Characteristic Raman peaks also expressed the same structural features. Microstructure analysis by FESEM showed the nanoflower structure of V205 with diameters in the range of 60-80 nm and length in 600-800 nm. A red-shift is observed in the characteristic absorption peak of V205, with the annealing, which attributed to the decrease of the bandgap of the samples.